Dynamics of a Upright Pole Coupled with Nonlinear Hysteretic Isolators under Harmonic Base Excitation - Yongfeng Cheng; Hulun Guo; Zhubing Zhu; Xiaochao Su; Yushu Chen (Shock and Vibration)
Leady isolator shows hysteretic nonlinearity. The isolation efficiency of leady isolator is an important problem in many engineering structures. In this paper, vibrations of a ceramic upright pole coupled with four leady isolators under harmonic base excitation are studied. A hysteretic force-deformation model of leady isolator is derived from experimental results. With this model, the vibration of the pole in rotation is studied. The frequency response is obtained analytically by employing harmonic balance method. The analytical results are agreed well with numerical results. The vibration of the pole is decreased greatly by leady isolator, especially near resonant case. The influences of system parameters on vibration response and resonant peak are discussed in detail.